Income Status and Medical History of Older Persons in Rawalpindi: Anthropology of Ageing (Medical Forum Monthly, 2024)
Objective: The aim of study is to highlight the hidden ageing population and its problems. The specific purpose of the study was to explore the interrelationship of ageing with income as well as the medical history among the older persons of Rawalpindi city.Study Design: Cross SectionalPlace and Duration of Study: This study was commissioned to the research team on behalf of Help Age Pakistan. The data collection was done in various union councils of Rawalpindi city. The study duration was three months of 2013.Materials and Methods: Structured questionnaire was developed to collect information on Older Persons’ health, economic and psychological status. In this regard, an extensive questionnaire was designed and pre-tested vigorously. Number of researchers form PMAS-Arid Agriculture University was engaged to collect data.Results: There is a strong relationship between the income statuses of OPs with their health physical conditions. The lack of permanent source of income leads to the high tendency of contracting various health problems among OPs. Similarly the inactive status of OPs also affects their health wellness which later on leads to create a multiplier effect regarding various health problems like heart problems, hypertensions, diabetes, arthritis, asthma, etc.Conclusion: There is a strong relation of income stability with the various psycho-somatic problems. The sense of being actively involved in familial functions especially economic chores provide a sense of independence and psychological sense of control over life results in better health among OPs.